Centronuclear Myopathy with Abundant Nemaline Rods in a Japanese Black and Hereford Crossbred Calf. (January 2020) - Kamio, K.; Takahashi, Y.; Ishihara, K.; Sekiya, A.; Kato, S.; Shimanuki, I.; Ide, M.; Furuoka, H.
Summary: Histopathological examination was performed on skeletal and diaphragmatic muscles from an 8-month-old male crossbred calf showing abnormal gait and tremor of the hindlimbs. There were numerous round fibres with centrally placed nuclei forming nuclear chains in longitudinal sections, associated with interstitial fibrosis or adipose tissue infiltration. On nicotinamide adenine dinucleotide tetrazolium reductase (NADH-TR) staining, some muscle fibres in severe lesions showed a spoke-like appearance due to a radial arrangement of sarcoplasmic strands. Additionally, increased NADH-TR activity in the subsarcolemmal structures, appearingas ring-like or necklace-like forms, were observed. Transmission electron microscopy revealed dilated sarcoplasmic reticulum and variably shaped electron-dense inclusions consisting of myofibrillar streams. Another prominent feature was the existence of numerous nemaline rods within muscle fibres; these were stained red by Gomori's trichrome stain. Immunohistochemistry revealed that the nemaline rods showed strong immunoreactivity with α-actinin and desmin antibodies. Electron microscopically, these structures were composed of dense-homogeneous material and continuous with the Z disk. The case was diagnosed as centronuclear myopathy with increased nemaline rods.